2004
DOI: 10.1021/jp037272j
|View full text |Cite
|
Sign up to set email alerts
|

Length Dependent Helix−Coil Transition Kinetics of Nine Alanine-Based Peptides

Abstract: It is well-known that end caps and the peptide length can dramatically influence the thermodynamics of the helix-coil transition. However, their roles in determining the kinetics of the helix-coil transition have not been studied extensively and are less well understood. Kinetic Ising models and sequential kinetic models involving barrier crossing via diffusion all predict that the helix formation time depends monotonically on the peptide length with the relaxation time increasing with respect to increasing ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
113
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(132 citation statements)
references
References 65 publications
(145 reference statements)
14
113
1
4
Order By: Relevance
“…1). A T-jump study on helix unfolding found that different s-values are required to describe the stability of helical peptides with varying lengths (18). In our study, in contrast, the same s-value describes the behavior of the different length peptides, which is in agreement with previous results by Rohl et al (15) and with the Lifson-Roig model.…”
Section: Resultssupporting
confidence: 78%
“…1). A T-jump study on helix unfolding found that different s-values are required to describe the stability of helical peptides with varying lengths (18). In our study, in contrast, the same s-value describes the behavior of the different length peptides, which is in agreement with previous results by Rohl et al (15) and with the Lifson-Roig model.…”
Section: Resultssupporting
confidence: 78%
“…This conclusion has been confirmed by simple lattice dynamics models (44,45) that revealed stretching factors ␤ Ͻ 1 with decreasing temperature. The kinetic effect of helix stabilization was investigated by Wang et al (30). For 19-mer peptides (length comparable with FK11X), the use of stabilizing capping residues resulted in acceleration and stretching of the kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…In FK11X, Lys has been replaced by Arg to further increase helicity (28), and a Gln residue is used for C-terminal capping (29). Capping has been observed not only to stabilize the helix but also to speed up folding (30). Two alanines at positions 3 and 14 have been replaced by cysteine to allow for the attachment of the photoswitchable linker.…”
mentioning
confidence: 99%
“…43 The fluctuating Hamiltonian is constructed for 100 snapshots obtained from a 2 ns MD trajectory generated earlier. 44 Figure 9 shows the 3D structure of SPE 3 from one MD snapshot and the distribution of Ramachandran angles.…”
Section: Linear Absorption and Vibrational CDmentioning
confidence: 99%